PENDAPATAN DAN KESEJAHTERAAN RUMAH TANGGA PETERNAK SUSU KAMBING ETAWA (Kasus Laboratorium Desa Universitas Lampung di Desa Sungai Langka Kecamatan Gedong Tataan Kabupaten Pesawaran) - Rosdiana, Iis; Haryono, Dwi; Endaryanto, Teguh (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This resarch aims to analyse income and house hold welfare of Etawa goat milk farmers in Sungai Langka Village, Gedong Tataan of Pesawaran District. The location was chosen purposively by the consideration that most farmers are Etawa goat. Primary and secondary data were collected in May - August 2018. Data are analyzed using quantitative and qualitative descriptive analyses. The research results showed that Etawa goat milk farming provided monthly income of Rp1,283,800.00. The farming is profitable with the R / C value of 3.17 over cash cost and 1.28 over total cost. Farmers’ welfare is included in prosperous category. Key words :Etawa goat, farmers, income, milk